Pemberdayaan Masyarakat Anti Narkoba di Lingkungan Dunia Usaha Swasta - Sumarliani, Sri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2022)
Narcotics distribution is currently not only in urban areas or in remote villages. The industrial community or work environment has a tendency for narcotics to be circulated illegally, especially in the business world where the workforce is mostly productive workers who are vulnerable to drug abuse and illicit trafficking. The role of the community in the work environment is needed in preventing P4GN (Prevention and Eradication of Narcotics Abuse and Illicit Trafficking). Eradication efforts are aimed at the community in a promotive and preventive manner. This community service aims to dig up information from the business environment in order to find solutions in overcoming P4GN (Prevention and Eradication of Narcotics Abuse and Illicit Trafficking). through FGD (Forum Group Discussion) among business actors. The method used is socialization and counseling to participants as well as the discussion method through FGD (Forum Group Discussion) among business actors. The results of this community service are expected to minimize the illicit trafficking of narcotics and the eradication of abuse by including in company rules and regulations, collective work agreements. Also in an effort to anticipate drug-free workers before becoming employees by showing a drug-free letter from the authorized agency, such as the Health Service, Hospitals, etc. Empowerment of the working community is needed through campaigns, counseling, education and training to workers in an effort to monitor and control illicit drug trafficking and be responsive to the environment in an effort to prevent illicit drug distribution in the business world